Composite spinel refractory material and preparation process thereof
By using high titanium slag in sintered spinel materials to reduce the melting temperature of magnesium oxide and chromium oxide, the formation of (Mg, Zn)(Cr, Al)2O4 composite spinel phase is promoted, and the problems of low material density and high melting point are solved, and efficient alkali vapor erosion and thermal shock resistance are achieved.
Patent Information
- Application Number
- CN202411786854.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The existing sintered spinel materials have low density and chromium-containing melting cast refractory materials have high melting point, resulting in poor performance in high temperature and alkali steam environments.
Using the low melting point of high titanium slag and the substitutability of Ti4+, the melting temperature of magnesium oxide and chromium oxide is reduced, the formation of (Mg, Zn)(Cr, Al)2O4 composite spinel phase is promoted, and the density of the material is improved and the resistance to alkali steam erosion.
The densification of the melt-cast composite spinel refractory material has been achieved, improving its performance in high temperature and alkali steam environments, including thermal shock resistance and alkaline slag corrosion resistance.
Abstract
Description
Technical Field
[0001] The invention relates to a composite spinel refractory material and a preparation process thereof, and belongs to the field of refractory materials of inorganic non-metallic material discipline. Background Art
[0002] With the development of oxy-fuel combustion technology in glass kilns, the flame temperature and radiation intensity in the kiln have increased, and the molten glass has volatilized to produce more alkali vapor, which has led to abnormal melting loss of traditional siliceous refractory materials and fused-cast zirconium corundum refractory materials during service, affecting the service life of the kiln. Magnesium-aluminum spinel, magnesium-chromium spinel, magnesium-iron spinel and other materials have stable spinel structures, and the refractory materials have good alkali corrosion resistance, high-temperature mechanical properties and thermal shock resistance, and have great application potential in oxy-fuel combustion glass kilns.
[0003] Patent CN100402470C discloses a highly thermal shock-resistant corundum-spinel refractory material and its preparation method. Although the invention ensures the high temperature performance of the material by compounding the spinel and alumina phases, and improves the thermal shock resistance of the material by reacting to generate aluminum titanate, it does not consider the volume expansion problem of the reaction of alumina and magnesium oxide to produce magnesium aluminum spinel and the problem of medium-temperature decomposition of aluminum titanate at 750~1300℃, and the volume stability of the material is difficult to guarantee. Patent CN102531646B discloses a high-purity aluminum-magnesium spinel brick refractory material for float glass full oxygen combustion melting furnace. Although the invention uses high-purity aluminum-magnesium spinel as a raw material to make the refractory product have the advantages of micro-impurities, relatively small specific gravity, low porosity, high strength, good thermal shock resistance, high refractoriness (>1800℃), acid and alkali resistance, etc., due to the stable crystal structure of magnesium aluminum spinel and the extremely low oxygen ion diffusion coefficient at high temperature, it is very difficult to obtain a dense body by sintering the high-purity magnesium aluminum spinel raw material.
[0004] The addition of chromium oxide and titanium oxide is beneficial to the densification of spinel. Patent CN105541351B discloses a composite spinel zirconium brick specially used for the top of the regenerator of a glass melting furnace and its manufacturing method. Although the invention produces an aluminum-chromium solid solution through reaction to ensure the corrosion resistance of the material, and introduces β-Al2O3 and zirconium raw materials to improve the product's resistance to alkaline corrosion and thermal shock resistance, it does not consider the difficulty of sintering and densifying zirconium oxide and chromium oxide, resulting in the presence of a large number of micropores and microcracks in the material after sintering, which is easily penetrated by alkali vapor, increasing the risk of material erosion. Patent CN103030410B discloses an aluminum-magnesium-chromium composite spinel brick. Although the invention forms an aluminum-magnesium-chromium spinel phase by solid dissolving chromium oxide into magnesium-aluminum spinel, thereby improving the corrosion resistance and high-temperature strength of the material, it is difficult to avoid the generation of micropores and microcracks due to the difficulty of sintering chromium oxide to densify. Patent CN107663097B discloses a high-performance dense composite titanium spinel brick and its manufacturing method. Although the invention introduces high-density and low-impurity dense composite titanium spinel to make the material have the characteristics of high slag erosion resistance, good thermal shock resistance, high density, low porosity, high compressive strength, etc., the thermal expansion coefficients of the magnesium aluminum spinel particles and the magnesium titanate in the matrix are quite different. During the sintering process, circumferential tensile stress is easily generated around the particles, resulting in the appearance of annular cracks, which affects the density of the material.
[0005] The fused-cast refractory material has a high degree of density and is superior in dealing with the penetration of alkali vapor. Patent CN102603341B discloses a fused-cast corundum-spinel brick for the side wall of an aluminum electrolytic cell and its preparation method. Although the invention uses nickel ferrite and alumina and magnesium oxide solid solution to make the material structure dense and low in porosity, when the alumina content in the fused-cast spinel refractory material is several times higher than that of magnesium oxide, a large amount of Mg will be generated. 2+ Ion vacancies lead to high grain boundary migration rate, which easily forms more micropores in the molten casting material. Patent CN114507077B discloses a molten zirconium-chromium-corundum refractory brick and its preparation method. Although the material has high density and good alkali corrosion resistance, the price of chromium oxide and zirconium oxide is high and the melting point is high, which leads to high material production cost.
[0006] In order to solve the problems of low density of existing sintered spinel materials and high melting point of chromium-containing refractory materials, the present invention utilizes high titanium slag with low melting point and Ti 4+ Can replace Mg 2+ and Cr 3+The characteristics of molten metal reduce the melting temperature of magnesium oxide and chromium oxide, promote the formation of (Mg, Zn)(Cr, Al)2O4 composite spinel phase, and make the fused-cast composite spinel refractory material dense while having excellent resistance to alkali vapor corrosion. At the same time, because the fused-cast composite spinel refractory material is not easily infiltrated by alkaline slag, it is also suitable for use in severely corroded parts of copper smelting industrial furnaces. Summary of the invention
[0007] With the development of oxy-fuel combustion technology in glass kilns, the flame temperature and radiation intensity in the kiln have increased, and the molten glass has volatilized to produce more alkali vapor, which has led to abnormal melting loss of traditional siliceous refractory materials and fused-cast zirconium corundum refractory materials during service, affecting the service life of the kiln. Magnesium-aluminum spinel, magnesium-chromium spinel, magnesium-iron spinel and other materials have stable spinel structures, and the refractory materials have good alkali corrosion resistance, high-temperature mechanical properties and thermal shock resistance, and have great application potential in oxy-fuel combustion glass kilns.
[0008] Patent CN100402470C discloses a highly thermal shock-resistant corundum-spinel refractory material and its preparation method. Although the invention ensures the high temperature performance of the material by compounding the spinel and alumina phases, and improves the thermal shock resistance of the material by reacting to generate aluminum titanate, it does not consider the volume expansion problem of the reaction of alumina and magnesium oxide to produce magnesium aluminum spinel and the problem of medium-temperature decomposition of aluminum titanate at 750~1300℃, and the volume stability of the material is difficult to guarantee. Patent CN102531646B discloses a high-purity aluminum-magnesium spinel brick refractory material for float glass full oxygen combustion melting furnace. Although the invention uses high-purity aluminum-magnesium spinel as a raw material to make the refractory product have the advantages of micro-impurities, relatively small specific gravity, low porosity, high strength, good thermal shock resistance, high refractoriness (>1800℃), acid and alkali resistance, etc., due to the stable crystal structure of magnesium aluminum spinel and the extremely low oxygen ion diffusion coefficient at high temperature, it is very difficult to obtain a dense body by sintering the high-purity magnesium aluminum spinel raw material.
[0009] The addition of chromium oxide and titanium oxide is beneficial to the densification of spinel. Patent CN105541351B discloses a composite spinel zirconium brick specially used for the top of the regenerator of a glass melting furnace and its manufacturing method. Although the invention produces an aluminum-chromium solid solution through reaction to ensure the corrosion resistance of the material, and introduces β-Al2O3 and zirconium raw materials to improve the product's resistance to alkaline corrosion and thermal shock resistance, it does not consider the difficulty of sintering and densifying zirconium oxide and chromium oxide, resulting in the presence of a large number of micropores and microcracks in the material after sintering, which is easily penetrated by alkali vapor, increasing the risk of material erosion. Patent CN103030410B discloses an aluminum-magnesium-chromium composite spinel brick. Although the invention forms an aluminum-magnesium-chromium spinel phase by solid dissolving chromium oxide into magnesium-aluminum spinel, thereby improving the corrosion resistance and high-temperature strength of the material, it is difficult to avoid the generation of micropores and microcracks due to the difficulty of sintering chromium oxide to densify. Patent CN107663097B discloses a high-performance dense composite titanium spinel brick and its manufacturing method. Although the invention introduces high-density and low-impurity dense composite titanium spinel to make the material have the characteristics of high slag erosion resistance, good thermal shock resistance, high density, low porosity, high compressive strength, etc., the thermal expansion coefficients of the magnesium aluminum spinel particles and the magnesium titanate in the matrix are quite different. During the sintering process, circumferential tensile stress is easily generated around the particles, resulting in the appearance of annular cracks, which affects the density of the material.
[0010] The fused-cast refractory material has a high degree of density and is superior in dealing with the penetration of alkali vapor. Patent CN102603341B discloses a fused-cast corundum-spinel brick for the side wall of an aluminum electrolytic cell and its preparation method. Although the invention uses nickel ferrite and alumina and magnesium oxide solid solution to make the material structure dense and low in porosity, when the alumina content in the fused-cast spinel refractory material is several times higher than that of magnesium oxide, a large amount of Mg will be generated. 2+ Ion vacancies lead to high grain boundary migration rate, which easily forms more micropores in the molten casting material. Patent CN114507077B discloses a molten zirconium-chromium-corundum refractory brick and its preparation method. Although the material has high density and good alkali corrosion resistance, the price of chromium oxide and zirconium oxide is high and the melting point is high, which leads to high material production cost.
[0011] In order to solve the problems of low density of existing sintered spinel materials and high melting point of chromium-containing refractory materials, the present invention utilizes high titanium slag with low melting point and Ti 4+ Can replace Mg 2+ and Cr 3+The characteristics of molten metal reduce the melting temperature of magnesium oxide and chromium oxide, promote the formation of (Mg, Zn)(Cr, Al)2O4 composite spinel phase, and make the fused-cast composite spinel refractory material dense while having excellent resistance to alkali vapor corrosion. At the same time, because the fused-cast composite spinel refractory material is not easily infiltrated by alkaline slag, it is also suitable for use in severely corroded parts of copper smelting industrial furnaces. DETAILED DESCRIPTION
[0012] Example 1
[0013] According to the following formula (weight and particle size content): (1) Chromium oxide sand 45%, (2) Industrial alumina 25%, (3) Magnesium oxide 20%, (4) High titanium slag (TiO2 weight percentage 85%, total iron weight percentage 10%) 9%, (5) Zinc oxide powder 1%.
[0014] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 200~260V and a melting current of 9000~12000A, and then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 1.0MPa melt; casting: preparing a sand mold by melting and casting composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 85:6, wherein the modulus of water glass is 3.5, and the melt is injected into the integral sand mold, and the casting temperature is 2000℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and the sand mold and the heat-insulating medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, it is made into a product that meets the size specifications. Example 2
[0015] According to the following formula (weight and particle size content): (1) Chromium oxide sand 25%, (2) Industrial alumina 35%, (3) Magnesium oxide 30%, (4) High titanium slag (TiO2 weight percentage 90%, total iron weight percentage 5%) 6%, (5) Zinc oxide powder 4%.
[0016] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 320~400V and a melting current of 3000~6000A, then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 0.2MPa melt; casting: preparing a sand mold by melting and casting a composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 100: 10, wherein the modulus of water glass is 2.8, injecting the melt into the integral sand mold, and the casting temperature is 1800℃℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and preheats the sand mold and the heat-insulating medium to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, a product that meets the size specifications is made. Example 3
[0017] According to the following formula (weight and particle size content): (1) Chromium oxide sand 38%, (2) Industrial alumina 30%, (3) 25% magnesia, (4) High titanium slag (TiO2 weight percentage 97%, total iron weight percentage 1%) 5%, (5) Zinc oxide powder 2%.
[0018] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 260~320V and a melting current of 6000~9000A, then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 0.7MPa melt; casting: preparing a sand mold by melting and casting composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 90:8, wherein the modulus of water glass is 3.1, and the melt is injected into the integral sand mold, and the casting temperature is 1900℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and the sand mold and the heat-insulating medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, it is made into a product that meets the size specifications. Comparative Example 1
[0019] According to the following formula (weight and particle size content): (1) Chromium oxide sand 35%, (2) Industrial alumina 35%, (3) Magnesium oxide 20%, (4) High titanium slag (TiO2 weight percentage 85%, total iron weight percentage 1%) 9%, (5) Zinc oxide powder 1%.
[0020] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 260~320V and a melting current of 6000~9000A, then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 0.7MPa melt; casting: preparing a sand mold by melting and casting composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 90:8, wherein the modulus of water glass is 3.1, and the melt is injected into the integral sand mold, and the casting temperature is 1900℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and the sand mold and the heat-insulating medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, it is made into a product that meets the size specifications.
[0021] Table 1 lists the performance of Comparative Example 1. Compared with Example 1, the preparation process is the same, but the weight ratio of industrial alumina / magnesia is 1.75, and the weight ratio of (2×magnesia-0.78×industrial alumina) / TiO2 in high-titanium slag is 1.66. Material analysis found the presence of Al2TiO5 and MgTi2O5 phases, both of which have the problem of decomposition leading to material performance degradation, and the material has poor resistance to alkaline slag corrosion. Therefore, it is necessary to "the weight ratio of industrial alumina / magnesia is 1.5, and the weight ratio of (2×magnesia-0.78×industrial alumina) / TiO2 in high-titanium slag ≥2.6". Comparative Example 2
[0022] According to the following formula (weight and particle size content): (1) Chromium oxide sand 39%, (2) Industrial alumina 25%, (3) Magnesium oxide 30%, (4) High titanium slag (TiO2 weight percentage 85%, total iron weight percentage 1%) 5%, (5) Zinc oxide powder 1%.
[0023] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 360~400V and a melting current of 9000~12000A, and then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 0.7MPa melt; casting: preparing a sand mold by melting and casting composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 90:8, wherein the modulus of water glass is 3.1, and the melt is injected into the integral sand mold, and the casting temperature is 2200℃; annealing: the outer part of the integral sand mold adopts a heat-insulating refractory material as a heat-insulating medium, and the sand mold and the heat-insulating medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, it is made into a product that meets the size specifications.
[0024] Table 1 lists the properties of Comparative Example 2. Compared with Example 1, the preparation process is the same, but the weight ratio of industrial alumina / magnesia is 0.83, and the weight ratio of (2×magnesia-0.78×industrial alumina) / TiO2 in high-titanium slag is 9.53. The melting temperature of the material is greatly increased, and large cracks are generated in the material after cooling. The thermal shock resistance of the material is poor. Therefore, it is necessary to "the weight ratio of industrial alumina / magnesia is 1~1.5, and the weight ratio of (2×magnesia-0.78×industrial alumina) / TiO2 in high-titanium slag is 2.6~6.1". Comparative Example 3
[0025] According to the following formula (weight and particle size content): (1) Chromium oxide sand 42%, (2) Industrial alumina 25%, (3) Magnesium oxide 20%, (4) High titanium slag (TiO2 weight percentage 85%, total iron weight percentage 10%) 9%, (5) Zinc oxide powder 4%.
[0026] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 200~260V and a melting current of 9000~12000A, and then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 1.0MPa melt; casting: preparing a sand mold by melting and casting composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 85:6, wherein the modulus of water glass is 3.5, and the melt is injected into the integral sand mold, and the casting temperature is 2000℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and the sand mold and the heat-insulating medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, it is made into a product that meets the size specifications.
[0027] Table 1 lists the properties of Comparative Example 3. Compared with Example 1, the preparation process is the same, but the weight ratio of zinc oxide powder to magnesia is 0.2. Compared with the example, the porosity of the material is significantly improved, and the slag penetration resistance is reduced. Therefore, it is necessary to "have a weight ratio of zinc oxide powder to magnesia of ≤0.15". Comparative Example 4
[0028] According to the following formula (weight and particle size content): (1) Chromium oxide sand 28%, (2) Industrial alumina 35%, (3) Magnesium oxide 30%, (4) High titanium slag (TiO2 weight percentage 90%, total iron weight percentage 5%) 6%, (5) Zinc oxide powder 1%.
[0029] The specific process steps include the following parts: batching: adding the raw materials into the mixer in proportion and mixing them evenly to form a batch material; melting: loading the batch material into an electric arc furnace, heating the batch material until it is completely melted at a melting voltage of 320~400V and a melting current of 3000~6000A, then inserting a hollow electrode into the melt, and continuously conducting oxygen into the 0.2MPa melt; casting: preparing a sand mold by melting and casting a composite spinel brick clinker, the weight ratio of which is molding sand: water glass = 100: 10, wherein the modulus of water glass is 2.8, injecting the melt into the integral sand mold, and the casting temperature is 1800℃℃; annealing: the outer part of the integral sand mold uses a heat-insulating refractory material as a heat-insulating medium, and preheats the sand mold and the heat-insulating medium to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; cold processing: through cutting, grinding, drilling and other processes, a product that meets the size specifications is made.
[0030] Table 1 lists the properties of Comparative Example 4. Compared with Example 2, the preparation process is the same, but the weight ratio of zinc oxide powder to magnesia is 0.03. Compared with Example 2, the material density is reduced and the slag penetration resistance is reduced. Therefore, it is necessary to "have a weight ratio of zinc oxide powder to magnesia of 0.05 to 0.15". Comparative Example 5
[0031] According to the following formula (weight and particle size content): (1) Chromium oxide sand 45%, (2) Industrial alumina 25%, (3) Magnesium oxide 20%, (4) High titanium slag (TiO2 weight percentage 85%, total iron weight percentage 10%) 9%, (5) Zinc oxide powder 1%.
[0032] The specific process steps include the following parts: batching: add the raw materials into the mixer according to the proportion, add lignin or phosphate binder and mix evenly; molding: press and mold with a 1000t press; drying: dry naturally for 36 hours, and then dry at 260℃ for 48 hours; firing: load the dried semi-finished product into a tunnel kiln and keep it warm at 1800℃ for 9 hours; cold processing: through cutting, grinding, drilling and other processes, it is made into products that meet the size specifications.
[0033] Table 1 lists the performance of Comparative Example 5. Compared with Example 1, the raw material formula is the same, and the sintering process is adopted. Although the formation of (Mg, Zn)(Cr, Al)2O4 composite spinel phase can be detected in the material, due to the influence of the solid-solid reaction rate and the limitation of the sintering process, the composite spinel phase in the material is significantly less than that of the material prepared by the melt-casting process, and there are still independent Cr2O3, MgO, and TiO2 phases. The material performance is significantly worse than that of the melt-cast material.
[0034] The performance comparison of the materials prepared in the above examples and the comparative examples is shown in Table 1: Table 1 Comparison of refractory properties index Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Bulk density g / cm 3 > 4.00 3.90 3.96 3.92 3.91 3.99 3.81 3.52 Apparent porosity% 2.0 1.8 1.7 6.7 4.2 3.6 3.1 13.4 Normal temperature compressive strength MPa 358 341 355 298 170 319 308 92 Resistance to high-alkali glass melt corrosion (mm, 1200℃×24h) 0.10 0.13 0.10 0.97 0.10 0.21 0.25 1.2 Anti-corrosion and penetration capacity of copper smelting slag (mm, 1500℃×24h) 0.16 0.17 0.15 2.1 0.16 0.35 0.40 3.4 Thermal shock resistance (1100℃, water cooling) >10 >10 >10 >10 7 >10 >10 >10
Claims
1. A composite spinel refractory material, the formula of which is as follows by weight percentage: (1) Chromium oxide sand 25~45%, (2) Industrial alumina 25~35%, (3) Magnesium oxide 20~30%, (4) High titanium slag 5~10%, (5) Zinc oxide powder 1~4%; (3) The weight percentage of TiO2 in the high titanium slag is ≥85%, and the weight percentage of total iron is ≤10%; The weight ratio of industrial alumina / magnesia is 1-1.5, and the weight ratio of (2×magnesia-0.78×industrial alumina) / TiO2 in high-titanium slag is 2.6-6.1; The weight ratio of the zinc oxide powder to the magnesia is 0.05 to 0.
15.
2. A process for preparing the composite spinel refractory material according to claim 1, comprising the following process steps: (1) Batching: Add the raw materials into the mixer according to the proportion and mix them evenly to form a batch material; (2) Melting: The batch material is loaded into an electric arc furnace and heated until it is completely melted. Then a hollow electrode is inserted into the melt and oxygen is blown into the melt. (3) Casting: The melt is poured into the integral sand mold at a casting temperature of 1800°C to 2000°C; (4) Annealing: The exterior of the integral sand mold uses insulating refractory materials as the heat preservation medium, and the sand mold and the heat preservation medium are preheated to ensure that the cooling rate in the annealing process is ≤0.15℃ / kg·h; (5) Cold processing: After cutting, grinding, drilling and other processes, the products are made into products that meet the size specifications.
3. The process according to claim 2, wherein in process (2), the melting voltage is 200-400 V, the melting current is 3000-12000 A, and the oxygen pressure continuously conducted from the hollow electrode is 0.2-1.0 MPa.
4. The process according to claim 2, wherein in process (3), the sand mold is made of fused-cast composite spinel brick clinker, and the weight ratio of the sand: water glass is 85-100:6-10, wherein the modulus of the water glass is 2.8-3.5.
Citation Information
Patent Citations
Thermal-knock resisting diamond spar-spinele refractory materials and its production
CN100402470C
High-purity Al-Mg spinel brick fireproof material for float glass oxy-fuel combustion melting furnace
CN102531646B
Fusion cast corundum-spinel brick for side wall of aluminum electrolytic bath and preparation method of fusion cast corundum-spinel brick
CN102603341B
Aluminum-magnesium-chromium composite spinel bricks
CN103030410B
Special composite spinel zirconium brick for the top of regenerator of glass melting furnace and its manufacturing method
CN105541351B